Influence of kaempferol and nutrients on arbuscular mycorrhizal colonization and growth of oil palm seedlings - Ahmad, Nur Walidah (2017)
Arbuscular mycorrhizal fungi (AMF) can form potentially beneficial associations with the roots of more than 80% of terrestrial plants. Plant roots release a wide range of compounds which are involved in complex communication processes in the rhizosphere. One of the alternative methods to decrease fertilizer application in oil palm is via AMF inoculation. Flavonoid exudates of oil palm roots can be important in the interaction between oil palm and AMF. This study aims to characterize the flavonoid in oil palm root exudates and determine the influence of this flavonoid on AMF colonization of oil palm roots. A series of experiments were thus conducted under laboratory and glasshouse conditions with the following objectives: i) to characterize the flavonoid secreted from oil palm root exudates; ii) to determine the effect of root flavonoids on the establishment of AMF in oil palm roots; and iii) to determine the effect of nitrogen and phosphorus on root exudate compositions, AMF colonization and oil palm growth. Oil palm root exudates were screened for flavonoid compounds using liquid chromatography. Kaempferol was identified as the flavonoid existing in the oil palm root exudates. The effect of kaempferol on the establishment of AMF in oil palm roots was then evaluated under glasshouse conditions, followed by study on the effects of nitrogen and phosphorus on flavonoid production. Exogenous kaempferol was applied in four concentrations (0, 2.5, 5.0 and 10.0 ppm) in two mycorrhiza treatments (Glomus mosseae and mixed AM species) and four fertilizer treatments (P0N0, P0N1, P1N0 and P1N1). The results showed that addition of kaempferol positively affected infection of G. mosseae, but not infection of the mixed AM species that contained a mixture of G. mosseae and Scutelospora sp. Hoagland nutrient solution was applied as the nutrient source. At sixth week of growth, the roots were harvested from the soil, and debris and soil particles washed off. The root development was observed through a root scanner. The results showed that kaempferol was the dominant flavonoid produced by the oil palm roots. The highest amount of flavonoid (42.57 mg mL-1) was secreted at 31 days of growth. Oil palm seedlings inoculated with G. mosseae in the presence of 10 ppm kaempferol showed improved growth compared to the plants inoculated with mixed AM species, in the treatments over a six week period. The second experiment proved that nitrogen and phosphorus fertilizers influenced AM colonization and growth of oil palm seedlings. The application of fertilizer resulted in this effect when the complete fertilizer requirement was applied. Plant growth was affected by G. mosseae at 10 ppm. The availability of P affects the plant biomass, in contrast to N. When complete fertilizer was applied, the G. mosseae inoculated plants showed the highest root infection at 10 ppm kaempferol, with 96.11 % infection. The N uptake was significant when complete fertilizer was given to the G. mosseae inoculated plants and non-inoculated plants, at 3.18 mg/plant (10 ppm) and 3.26 mg/plant (0 ppm), respectively. Application of AMF and kaempferol significantly affected oil palm root development.